DEPENDENCE OF TENSILE FORCE OF THE ELASTIC LIMIT STATE OF ROPES FROM THE BENDING PARAMETER ON THE DRUM (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
Based on the method previously developed by the authors for the analytical determination of the ultimate elastic state of the ropes, the dependence of the  tensile force with the winding of the rope on the drum on the parameter  (the ratio of the diameters of the drum and the rope) in the interval . Dependence  was determined for two loading schemes of rope: stretching of the rope with winding on the drum with a freely suspended load and stretching of the rope with winding on the drum with the load in the guides. Based on the developed method, the dependence of  was performed for 16 kantais of different designs. The tensile strength is presented in the relative form  (  total breaking strength of the rope wires). The effort  significantly depends on the construction of the rope and the bending parameter . In the section  the force  increases monotonically and practically linearly, reaching the value corresponding to the calculation scheme of stretching a straight rope. For different structures with the parameter  change in force  with . In the section  the dependence  is not linear, at . The section  is characterized by a sharp change in force , with the bending parameter . For most rope designs at  the forces  are close to zero values. When stretching with a freely suspended load, the forces  are 1.6–1.7 times lower than when stretching in guides. For twisting ropes (one-way winding), the ratio is 2.5–3.4 times. In the normative methods of calculations of lifting ropes, the characteristics  or  are used, which do not take into account the peculiarities of the deformation and construction of the ropes. We believe that the given information is appropriate in solving the issue of building a methodology for calculating the static strength of lifting ropes based on the characteristics of their ultimate elastic state, which will ensure stable optimality of the use of ropes, will allow you to rationally choose the type of rope construction and its dimensions.
Keywords: rope; strength characteristics; calculation scheme; bending parameter when winding on a drum; calculation method for static strength.